Laparoscopic resection of a bulky primary adrenal hydatid cyst - Walter Nardi (Journal of Minimal Access Surgery, 2015)
A 55-year-old man with no medical history of relevance was referred to our department for chronic back pain. Plain radiographs of the abdomen showed a round calcified image with liquid level inside in the upper-left quadrant. On computed tomography (CT) a bulky solid-cystic mass with calcified wall of 65 × 34 mm was shown in the left adrenal gland with no-contrast enhancement. The patient underwent a laparoscopic approach. Intraoperatively there was a large hard stony mass depending on the left adrenal gland, which was entirely supplanted by the tumor. Complete excision was done. The patient underwent uneventful recovery. Histopathology examination showed a solid-cystic mass with a thick fibrous wall and calcified areas compatible with hydatid cyst. To date there have been published few cases of adrenal hydatid cyst. To our awareness it is the fourth case issued in all literature resected by the laparoscopic approach.